Critical vulnerabilities for diversion of controlled substances in the emergency department: Observations and healthcare failure mode and effect analysis. Issue 3 (June 2023) - de Vries, Maaike; Fan, Mark; Tscheng, Dorothy; Hamilton, Michael; Trbovich, Patricia
Objectives: Drug theft by healthcare workers is a recognized problem in emergency departments (EDs) that can lead to patient, healthcare worker, and organization harm. Diversion takes various forms, including tampering with syringes, pilfering from waste containers and falsely documenting drug administration. Before implementing risk-mitigating interventions, we need a detailed understanding of the vulnerabilities in ED medication-use processes. This study sought to identify the critical failure modes (CFMs) within EDs that increase diversion risk and characterize the system factors contributing to CFMs. Methods: Between June 2018 and February 2019, we conducted observations in two Ontario EDs. Observers recorded tasks carried out by nurses, pharmacists, and physicians. We performed a Healthcare Failure Mode and Effect Analysis, informed by the observation data, to proactively identify CFMs in the medication-use processes. Failure modes were coded for their effects on diversion risk and the contributing system factors. Results: We identified 28 CFMs that increase diversion risk by enabling inappropriate access to controlled substances or compromising documentation. CFMs are multifactorial, stemming primarily from factors related to person (e.g., intent to divert) and tools/technology (e.g., limited automatic reconciliation of records), followed by organization (e.g., practices that diffuse accountability), environment (e.g., workspaces that obscure illicit behaviours), and task (e.g., unstructured processes leading to lapses). Conclusion: The study findings inform opportunities to revise vulnerable processes and bolster safeguards, decreasing diversion risk and protecting patients and healthcare workers.